Experimental Soil Warming and Permafrost Thaw Increase CH4 Emissions in an Upland Tundra Ecosystem. Issue 11 (5th November 2021) - Taylor, M. A.; Celis, G.; Ledman, J. D.; Mauritz, M.; Natali, S. M.; Pegoraro, E.‐F.; Schädel, C.; Schuur, E. A. G.
Abstract: Rapid Arctic warming is causing permafrost to thaw and exposing large quantities of soil organic carbon (C) to potential decomposition. In dry upland tundra systems, subsidence from thawing permafrost can increase surface soil moisture resulting in higher methane (CH4 ) emissions from newly waterlogged soils. The proportion of C released as carbon dioxide (CO2 ) and CH4 remains uncertain as previously dry landscapes transition to a thawed state, resulting in both wetter and drier microsites. To address how thaw and moisture interact to affect total C emissions, we measured CH4 and CO2 emissions from paired chambers across thaw and moisture gradients created by nine years of experimental soil warming in interior Alaska. Cumulative growing season (May–September) CH4 emissions were elevated at both wetter (216.1–1, 099.4 mg CH4 ‐C m −2 ) and drier (129.7–392.3 mg CH4 ‐C m −2 ) deeply thawed microsites relative to shallow thaw (55.6–215.7 mg CH4 ‐C m −2 ) and increased with higher deep soil temperatures and permafrost thaw depth. Interannual variability in CH4 emissions was driven by wet conditions in graminoid‐dominated plots that generated >70% of emissions in a wet year. Shoulder season emissions were equivalent to growing season CH4 emissions rates in the deeply thawed, warmed soils, highlighting the importance of non‐growing season CH4 emissions. Net C sink potential was reduced in deeply thawed wet plots by 4%–42%, and by 3.5%–8% in deeply thawed drier plots due to anaerobic respiration, suggesting that some dry upland tundra landscapes may transition into stronger CH4 sources in a warming Arctic. Plain Language Summary: The Arctic is warming twice as fast as the global average. This is causing permafrost to thaw and subside. Soil carbon decomposition under these conditions can be released as carbon dioxide in dry soils, or as methane in newly waterlogged soils, which has a stronger global warming potential. We artificially warmed permafrost soils to measure how thaw and moisture affect total carbon emissions in a dry, upland tundra ecosystem. Methane emissions were higher with deeper thaw and wetter soils, especially in plots with sedge tussocks. Permafrost thaw increased soil moisture and we expect that this will lead to increased methane emissions from even dry landscapes in the future. Key Points: Hotspots accounted for 72% of growing season methane emissions in a wet year in patches where sedges dominated the plant community Thawed soil volume was a strong driver of increased methane emissions, even in the absence of high surface moisture Increased methane emissions with deep thaw reduced net growing season carbon uptake by 18% in wet areas, and 4% in drier areas